Acute Complete Oculomotor Nerve Palsy in a Young Male Due to a Skull Base Myofibroma. Issue 4 (December 2021) - Hoang, Tung Thanh; Van Le, Thuy; Tran, Dat; Ho, Thuong Duc; Thi Le, Nhung Hong; Subramanian, Prem S.
Abstract : Abstract: A 25-year-old male patient visited the ophthalmology clinic because of upper eye lid ptosis in the right eye, binocular double vision, and light sensitivity. He was diagnosed with a complete third nerve palsy caused by a skull base myofibroma, a rare clinical entity that has not been described before in oculomotor nerve palsy.